Some Sufficient Conditions For Starlikeness And Convexity - Nunokawa, Mamoru; Owa, Shigeyoshi; Çağlar, Mert; Yavuz Duman, Emel; POLATOĞLU, YAŞAR (Scientific Technical Research Council Turkey-Tubitak, Ataturk Bulvari No 221, Kavaklidere, Tr-06100 Ankara, Turkey, 2010)
There are many results for sufficient conditions of functions f (z) which are analytic in the open unit disc U to be starlike and convex in U. In view of the results due to S. Ozaki, I. Ono and T. Umezawa (1956), P.T. Mocanu (1988), and M. Nunokawa (1993), some sufficient conditions for starlikeness and convexity of f (z) are discussed.
Keywords: Univalent; starlike; convex; kimyasal bağ yapabilen; dışbükey